Pipecolic Acid, a Drought Stress Modulator, Boosts Chlorophyll Assimilation, Photosynthetic Performance, Redox Homeostasis, and Osmotic Adjustment of Drought-Affected Hordeum vulgare L. Seedlings - Nagihan Aktas; Saad Farouk; Amal Ahmed Mohammed Al-Ghamdi; Ahmed S. Alenazi; Mona Abdulaziz Labeed AlMalki; Burcu Seckin Dinler (Plants, 2025)
While pipecolic acid (Pip) mediates morpho-physiological and molecular responses during biotic stress, its roles under drought remain an inexpressible mystery. The investigation aimed to elucidate the roles of a 30μM Pip pretreatment in alleviating drought injury on barley (Hordeum vulgare L. cv, Bülbül89) seedlings. Pip pretreatment under normal or drought conditions lowered the osmotic potential (Ψs) and water saturation deficit (WSD), while optimizing the relative water content (RWC), triggered osmotically energetic molecules (OEM) and salicylic acid (SA) accumulation, improving osmotic adjustment (OA), and boosting water retention and uptake capacity (WTC, and WUC), alongwith a considerable improvement in seedling growth over non-treated plants under such conditions. Additionally, Pip pretreatment improved chlorophyll (Chl), the chlorophyll stability index (CSI), pheophytina, chlorophyllidea (chlidea), chlorophyllideb (chlideb), chla/chlidea, chlb/chlideb, protoporphyrin, Mg-protoporphyrin, protochlorophyllide, and photosynthetic performance over non-treated plants under such conditions. Pip pretreatment preserves redox homeostasis in drought-stressed plants by accumulating antioxidant solutes alongside the activation of superoxide dismutase and glutathione reductase over non-treated plants. Drought distinctly reduced Ψs (more negative), RWC, photosynthetic pigment, CSI, chlorophyll assimilation intermediate, and photosynthetic performance, with an increment in chlorophyll degradation intermediate and nonenzymatic antioxidant solutes. Drought maintains OA capacity via a hyper-accumulation of OEM and SA, which results in higher WSD, WTC, and WUC. Drought triggered an oxidative burst, which was associated with a decline in the membrane stability index. These findings highlight Pip’s capability for lessening drought stress-induced restriction in barley seedlings via bolstering oxidative homeostasis, OA capacity, and stabilizing chlorophyll biosynthesis. Future research must elucidate the precise molecular mechanisms underlying Pip’s action in alleviating drought injury.